FILM “KEHORMATAN DI BALIK KERUDUNG” SEBAGAI LIVING AL-QURAN - Muttaqin, Ahmad (IAIN Pekalongan, 2016)
The film,“Kehormatan di Balik Kerudung” (read: KdBK) is a religious Indonesian film containing gender issues.In relation to this, it is necessary to view this movie as livingAlQuranphenomenon. By using femenism approach, this paper concludes that first, the“KdBK” movie contains gender issue as reception from Q.S. Ali ‘Imran (3): 132. Second, many gender imbalance issues are showed from this movienamely, discrimination, stereotype, subordination, marginal issue and double burden.Film,